Effective Listening. - Bailey-Hughes, Brenda; Kolovou, Tatiana (linkedin.com, 2015)
Communications experts Tatiana Kolovou and Brenda Bailey-Hughes help you assess your listening skills and develop more-effective listening behaviors.